2022
DOI: 10.1002/hsr2.978
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and the increase in schizophrenia incidence in the future: A hypothesis and a serious warning

Abstract: Background and Aims The coronavirus disease 2019 (COVID‐19), which has caused a global pandemic, is brought on by the Acute Respiratory Syndrome coronavirus 2 (SARS‐CoV‐2). Since the COVID‐19 pandemic started so recently, dealing with complications that emerge years later and have the potential to cause several crises for humanity is one of the issues we face in the post‐COVID‐19 age. Therefore, we wish to discuss a theory and potential dangers surrounding the probability of schizophrenia followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In our case, at the 6-month and 1-year follow-up, the patient was in complete remission without any evidence of chronic psychosis. In view of current concerns regarding an increased risk of schizophrenia following COVID-19 [ 64 ], future follow-up cohort studies are highly needed.…”
Section: Discussion and Brief Review Of Literaturementioning
confidence: 99%
“…In our case, at the 6-month and 1-year follow-up, the patient was in complete remission without any evidence of chronic psychosis. In view of current concerns regarding an increased risk of schizophrenia following COVID-19 [ 64 ], future follow-up cohort studies are highly needed.…”
Section: Discussion and Brief Review Of Literaturementioning
confidence: 99%
“… 8 , 9 Protecting the mental health of these patients is therefore important not only for their own long-term health but also for controlling the pandemic. 10 , 11 …”
Section: Introductionmentioning
confidence: 99%
“… 12 It can be said that COVID‐19 can cause several changes in the human immune system that are known possible etiologies of schizophrenia. 11 Previous studies have shown that COVID-19 has various psychosocial effects on schizophrenia patients. 4 , 13 , 14 At the same time, SARS-CoV-2 infection might present as liver injury, kidney injury, cardiac failure and mitochondriopathy.…”
Section: Introductionmentioning
confidence: 99%
“…Coronavirus infection itself may exacerbate symptoms in people with schizophrenia, as coronaviruses may be associated with symptoms of psychosis through an immune-related mechanism [11]. It can be said that COVID-19 can cause several changes in the human immune system that are known possible etiologies of schizophrenia [12]. Previous studies have shown that COVID-19 has various psychosocial effects on schizophrenia patients [5,7,13].…”
Section: Introductionmentioning
confidence: 99%